Analysis of changes in the organizational structure of municipal offices = Główne determinanty struktury organizacyjnej urzędów gmin - Snopko, Joanna (Zielona Góra: Faculty of Economics and Management Press)
The multitude of tasks and problem issued faced by local governments necessitates their evolution towards improvement of the existing organisational structures. Comparison of the existing organisational structures of various municipal offices could create a misleading that their organizational structures do not undergo any transformations. In reality, the type of an organisational structure remains unchanged while its elements change very frequently. These changes are activated when, according to the office management, they do not ensure proper performance of tasks faced by local government administration and appropriate customer service.
Keywords: struktura organizacyjna; specjalizacja; formalizacja; biurokracja; badania struktur organizacyjnych; urzędy gmin; organizational structure; specialization; formalization; red tape; stady of organizational structures; municipal offices